Characteristics of Alcohol-Free Hand Sanitizer Containing Eucheuma spinosum Extract as An Active Compound - Santhy Wisuda Sidauruk; Andarini Diharmi; N Ira Sari; Febriani Melisa Sinurat (Fakultas Perikanan dan Kelautan, Universitas Riau, 2021)
Eucheuma spinosum, red algae, contains secondary metabolites that act as antibacterial. It can be used as an active compound in the production of alcohol-free hand sanitizer. This research was aimed to determine the gram-positive and gram-negative antibacterial activity, pH, and viscosity of alcohol-free hand sanitizer containing E. spinosum extract. The results showed that the alcohol-free hand sanitizer containing 8% E. spinosum extract had characteristics in the form of a gel with the antibacterial activity of gram-positive bacteria (Bacillus subtilis) of 8.83±0.76 mm and gram-negative bacteria (Escherichia coli) of 8.67±0.58 mm, pH appropriate to pH of skin human (5.83±0.29), and viscosity following the hand sanitizer standard (2708 cps).